Bioremediation of heavy metals from electronic waste dumping sites with bacteria - Husnain Ahmad Khan; Shahid Sher; Dilara Abbas Bukhari; Abdul Rehman (Current Research in Biotechnology)
Samples were collected from two e-waste dumping sites (Mehmood Booti (31°36′28″N, 74°23′36″E) and Lakhodair (31°37′36.6″ N, 74°25′07.6″ E)) in Lahore, Pakistan. A portable multiparameter was used to determine physicochemical parameters such as temperature, pH, electrical conductivity, turbidity, total suspended particles, and total dissolved solids. Minimal salt broth was used for the determination of the minimal inhibitory concentration of the bacterium against all heavy metals. Bacterial morphology was observed under a scanning electron microscope with and without metal stress. The temperature range for all these samples was 28.7 to 35.7 °C, while the pH range was 6.7 to 7.89. The other parameters range, such as electrical conductivity µS/cm (698–8742), turbidity (14.2–103), total suspended particles (31–698), and total dissolved solids (564–23456). The lead concentration in the Mehmood Booti soil sample was 1800 mg/kg, while in the Lakhodair soil, it was 1567 mg/kg. Microbacterium sp. strain 1S1 was utilized for bioremediation assay at the lab and pilot scale. The resistance capacity of this bacterium against different metals was in the following order: As > Pb > Cd > Cu > Cr > Ni. The bioremediation potential of the bacterium against arsenic was 81.33 % and 96 % after 2 and 4 days. The least activity was observed against nickel, which was 17 and 28.33 % after 2 and 4 days. The metal removal capacity per CFU was the maximum for lead and arsenic compared to other metals, which were 1.99E-7 and 1.45E-07. The heat-inactivated bacterial cells removed arsenic in higher concentrations and lead in lower concentrations. The electron microscopy showed no significant alteration in bacterial morphology in control and metal-treated bacterial cells. The nanopore long-read sequencing analysis revealed that cadmium, nickel, copper, and arsenic resistance genes were found on the bacterial genome. No genes were found for lead and chromium but 849 hypothetical coding sequences having unknown functions were present on the bacterial genome. So, the Microbacterium sp. strain 1S1 is a potential candidate for the removal of heavy metals from e-waste dumping sites.